'Imagined communities': Reconsidering European Shakespeares. Issue 1 (July 2018) - Schülting, Sabine
Focusing on two productions of this past decade of The Merchant of Venice in Germany, the article challenges the predominant national focus of 'European Shakespeares'. It suggests that contemporary Shakespeare productions can indeed comment on Europe's intricate relations – political, economic and cultural – with other parts of the world, and on the tension between English as a lingua franca and the cultural and linguistic diversity of Europe. It suggests to complicate, with Shakespeare, the notion of 'European identity', in a time of mass migration, multi-ethnic societies and the globalization of economy, media and the arts.